Robust vaccine formulation produced by assembling a hybrid coating of polyethyleneimine–silica. Issue 3 (7th January 2016) - Wang, Guangchuan; Zhou, Hangyu; Nian, Qing-Gong; Yang, Yuling; Qin, Cheng-Feng; Tang, Ruikang
Abstract : Inspired by biomineralized core–shell structures, we suggest a polyethyleneimine–silica hybrid coated vaccine formulation to improve both thermostability and immunogenicity. Abstract : Exploring formulations that can improve the thermostability and immunogenicity of vaccines holds great promise in advancing the efficacy of vaccination to combat infectious diseases. Inspired by biomineralized core–shell structures in nature, we suggest a polyethyleneimine (PEI)–silica–PEI hybrid coated vaccine formulation to improve both thermostability and immunogenicity. Through electrostatic adsorption, in situ silicification and capping treatment, a hybrid coating of silica and PEI was assembled around a vaccine to produce vaccine@PEI–silica structures. Both in vitro and in vivo experiments demonstrated that the thermostability and immunogenicity of the modified vaccine were significantly improved. The modified vaccine could be used efficiently after long-term exposure at room temperature, which would facilitate vaccine transport and storage without a cold chain. Furthermore, mechanistic studies revealed that the PEI–silica–PEI coating acted as a physiochemical anchor as well as a mobility-restricting hydration layer to stabilize the enclosed vaccine. This achievement demonstrates a biomimetic surface-modification-based strategy to confer desired properties on biological products.